Acta Veterinaria Scandinavica - Agerholm, Jorgen S.
Acta Veterinaria Scandinavica is an open access journal encompassing all aspects of veterinary research and medicine of domestic and wild animals. Acta Veterinaria Scandinavica is the official journal of the Veterinary Associations of the Nordic Countries but welcomes submissions from veterinary colleagues worldwide. Founded in 1959, Acta Veterinaria Scandinavica became an online, open access publication in 2006.